Sodium-bile acid co-transporter is crucial for survival of a carcinogenic liver fluke Clonorchis sinensis in the bile. - Fuhong Dai; Won Gi Yoo; Yanyan Lu; Jin-Ho Song; Ji-Yun Lee; Youngro Byun; Jhang Ho Pak; Woon-Mok Sohn; Sung-Jong Hong (Public Library of Science (PLoS), 2020)
The liver fluke Clonorchis sinensis inhabits the bile ducts, where bile concentration disparities across the fluke cell membrane can cause bile intoxication. Sodium-bile acid co-transporter (SBAT) plays a crucial role in bile acid recycling. The process by which SBAT imports bile acids is electrically coupled to sodium ion co-transportation. Here, we report that the SBAT of C. sinensis (CsSBAT) is involved in bile acid transportation. CsSBAT cDNA encoded a putative polypeptide of 546 amino acid residues. Furthermore, CsSBAT consisted of ten putative transmembrane domains, and its 3D structure was predicted to form panel and core domains. The CsSBAT had one bile acid- and three Na+-binding sites, enabling coordination of a symport process. CsSBAT was mainly localized in the mesenchymal tissue throughout the fluke body and sparsely localized in the basement of the tegument, intestinal epithelium, and excretory bladder wall. Bile acid permeated into the adult flukes in a short time and remained at a low concentration level. Bile acid accumulated inside the mesenchymal tissue when CsSBAT was inhibited using polyacrylic acid-tetradeoxycholic acid conjugate. The accumulated bile acid deteriorated the C. sinensis adults leading to death. CsSBAT silencing shortened the lifespan of the fluke when it was placed into bile. Taken together, we propose that CsSBAT transports bile acids in the mesenchymal tissue and coordinate with outward transporters to maintain bile acid homeostasis of C. sinensis adults, contributing to C. sinensis survival in the bile environment.